Identification and leveling of psychological, cultural, and social effective factors on sustainable sexual health based on interpretive structural equations - hesam akbarzadeh; hasan maleki; mahbobeh khosravi; hosein skandari; shamsosadat zahedi (مجله علوم روانشناختی, 2023)
Background: Today, sexual health and providing the context for its realization has become a discourse and a sustainable goal in development, which has been pushed to the center of attention of politicians, experts, and researchers due to the problems arising from the unfavorable global conditions in this field. Aims: This research aimed to identify and stratify psychological, cultural, and social factors on sexual health based on the interpretive structural equation model. Methods: This research was carried out in a descriptive survey, in the first part, the dimensions and components related to stable sexual health were calculated and in the second part, the evaluation and leveling of these components were done. In the content analysis section, the society and the research environment are all first-hand and second-hand sources, including books, articles, specialized sites, upstream documents, pamphlets, and publications, which were of interest to the researcher to study the factors of sexual health development. In the stratification section, the statistical population consisted of all experts in the field of studies related to sexual health education, sex education, education, and family psychology, and 16 people were selected as a statistical sample using the purposeful sampling method. The data collection tool in the content analysis section was the content analysis worksheets of the first and second sources in line with the research objectives and their classification. In the stratification section, in order to determine the cause and effect of the extracted factors and their stratification, a questionnaire was created by the researcher. Which was designed based on the ISM model, was used, and in order to analyze the data, the interpretive structural modeling approach was used to provide a model of sustainable sexual health development factors. Results: The results showed the recognition of sexual rights, respect for sexual rights, education of cultural and social values in this field, respect for cultural differences under the title of cultural and social factors; Teaching the expression of sexual tendencies in childhood, teaching issues related to the growth and needs of adolescents, raising awareness of sexual development in adolescence, strengthening sexual identity, building self-confidence, and teaching healthy reproductive issues under the heading of psychological factors were prioritized. Conclusion: Achieving sexual health requires continuous education since childhood, which should be done sustainably, and it is necessary to achieve this kind of health education and empowerment of children in the psychological, cultural, and social fields